PD.06 Implementation barriers experienced by midwives when advising obese pregnant woman about physical activity: A cross-sectional survey. (9th June 2014) - McParlin, C; Robson, SC; Araujo-Soares, V; Carrick-Sen, D; Bell, R
Abstract : Introduction: Increasing levels of physical activity (PA) may help to reduce the risk of some obesity related pregnancy complications and NICE guidelines advise at least 30 minutes of moderate PA per day. However, women receive limited advice concerning PA from midwives. This study investigated perceived implementation difficulties for midwives advising obese pregnant women regarding PA. Methods: A self-completion, anonymous questionnaire was distributed to all midwives employed by three Trusts in Tyne and Wear (n = 365; response rate 52.6%). It was designed to identify barriers to midwives 'discussing PA with obese pregnant women and advising them in accordance with national guidelines'. The design used the Theoretical Domain Framework approach proposed by Michie (2005), which describes 11 domains of behavioural determinants used to investigate perceived implementation difficulties. Results: Midwives scored highest on knowledge, social-professional role and beliefs about consequences and lowest on skills, beliefs about capabilities and environment/context/resources domains. There were no differences in mean domain scores between hospital Trusts but midwives providing antenatal care scored higher than ward midwives, indicating they perceived fewer barriers to the behaviour. Regression analysis indicated that skills and memory/attention/decision domains had a significant influence on discussing /advising on PA. Conclusions: Midwives feel knowledgeable about PA advice for obese women and believe it is part of their role, but perceive they lack necessary skills, capabilities and resources. Designing interventions that improve skills, promote routine enquiry regarding PA and provide resources (eg. Information, referral pathways) may help improve midwives' PA advice. Reference: Michie S, et al . Quality and Safely in Health Care 2005;14:36–35